2009
DOI: 10.1118/1.3232001
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characterization of round HDR AccuBoost applicators for breast brachytherapy

Abstract: Monte Carlo benchmarking simulations of the HDR 192Ir source using the MCNP5 radiation transport code indicated agreement within 1% of the published results over the radial/angular region of interest. Changes in phantom size and radius did not cause noteworthy changes in the central axis depth-dose. Polynomial fit depth-dose curves provide a simple and accurate basis for a nomogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 10 publications
(11 reference statements)
1
29
0
Order By: Relevance
“…In their 2009 article describing experimental validation of the MC modeling of D-shaped AccuBoost applicators, Yang and Rivard (4) used a model 23343 Markus chamber for their absolute dose measurements using an N D,W ADCL factor for 60 Co, with acceptable results. This was further corroborated by Rivard et al (5) for the round applicators. A discussion with the authors confirmed that they used a 60 Co N D,W factor without attempting to establish a k Q factor for 192 Ir, and they did not employ a phantom correction factor for the solid phantoms used.…”
Section: E Determination Of An Absolute Dose Measurement Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…In their 2009 article describing experimental validation of the MC modeling of D-shaped AccuBoost applicators, Yang and Rivard (4) used a model 23343 Markus chamber for their absolute dose measurements using an N D,W ADCL factor for 60 Co, with acceptable results. This was further corroborated by Rivard et al (5) for the round applicators. A discussion with the authors confirmed that they used a 60 Co N D,W factor without attempting to establish a k Q factor for 192 Ir, and they did not employ a phantom correction factor for the solid phantoms used.…”
Section: E Determination Of An Absolute Dose Measurement Methodssupporting
confidence: 67%
“…Treatment planning is accomplished using a nomogram based on Monte Carlo (MC) modeling developed by Rivard et al (M.J. Rivard, personal correspondence via email, April 2013), which determines dwell times and position to deliver a given dose at the midplane of the compressed breast. While confirmatory measurements were performed by Yang and Rivard (4) and Rivard et al, (5) we are not aware of any published or independent recommendations for clinical commissioning of the AccuBoost system. We therefore conducted an extensive set of commissioning measurements in our clinic to validate the performance for the treatment delivery components of the AccuBoost system prior to clinical use.…”
mentioning
confidence: 99%
“…AccuBoost ® procedures use an HDR Ir-192 source in this applicator to deliver radiation to breast lesions (Rivard et al, 2009). To minimize the anisotropy of an HDR source, the applicator positions the source’s long axis normal to the applicator’s central axis (Nath et al, 1995, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…MC simulations were performed using the MCNP5 radiation transport code ͑v 1.40͒ for eight conical applicators to complement previous simulations performed for the round applicators using identical methods. 2 The reader is referred to work by Yang and Rivard and Rivard et al for specifics on the MC methods. 1,2,4 As modeled in the MC environment, cross-sectional views of the 6C19 and 6C25 conical applicators are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The AccuBoost ͑Advanced Radiation Therapy LLC, Tyngsboro, MA͒ D-shaped and round applicators have been dosimetrically characterized by Yang and Rivard 1 and by Rivard et al 2 in 2009. Both applicator types are used as an alternative to conventional electron beam breast boost irradiation.…”
Section: Introductionmentioning
confidence: 99%